Structural degradation of Thar lignite using MW1 fungal isolate: Optimization studies. (May 2015) - Haider, Rizwan; Ghauri, Muhammad A.; Jones, Elizabeth J.; Orem, William H.; SanFilipo, John R.
Abstract: Biological degradation of low-rank coals, particularly degradation mediated by fungi, can play an important role in helping us to utilize neglected lignite resources for both fuel and non-fuel applications. Fungal degradation of low-rank coals has already been investigated for the extraction of soil-conditioning agents and the substrates, which could be subjected to subsequent processing for the generation of alternative fuel options, like methane. However, to achieve an efficient degradation process, the fungal isolates must originate from an appropriate coal environment and the degradation process must be optimized. With this in mind, a representative sample from the Thar coalfield (the largest lignite resource of Pakistan) was treated with a fungal strain, MW1, which was previously isolated from a drilled core coal sample. The treatment caused the liberation of organic fractions from the structural matrix of coal. Fungal degradation was optimized, and it showed significant release of organics, with 0.1% glucose concentration and 1% coal loading ratio after an incubation time of 7 days. Analytical investigations revealed the release of complex organic moieties, pertaining to polyaromatic hydrocarbons, and it also helped in predicting structural units present within structure of coal. Such isolates, with enhanced degradation capabilities, can definitely help in exploiting the chemical-feedstock-status of coal. Highlights: Fungal isolate MW1 appeared to liberate organics from structural matrix of coal. Likewise, 1% coal loading ratio was found to be effective for coal degradation. Optimization studies showed the 0.1% glucose concentration efficient. Released organics belonged to the category of polyaromatic hydrocarbons.